2022
DOI: 10.1021/acs.iecr.2c01208
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Drag Force of Interactive Particles in Supercritical Water

Abstract: The drag of interactive particles in supercritical water (SCW) is studied by simulation. The difference in drag force between the leading particle and isolated particle is relatively small. The drag ratio between the trailing particle and leading particle is mainly analyzed. It is found that the variation trends of drag ratio in SCW are similar to that in fluids with constant properties. In particular, physical properties of SCW also have a special effect on drag ratio of the trailing particle. However, the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Table 3 shows the previous SCW flow around particle validation conclusions of our research group studies, 31,32 Wei et al, 22,38 and Zhang et al, 27,28 which shows the accuracy and reliability of the numerical model. Our group's previous studies 34,35,39 further showed more details for the multi-particle system. In summary, the accuracy of the calculation method adopted in this paper is verified, and it can be used in the subsequent numerical simulation calculation studies related to the particle layer.…”
Section: Numerical Model Validationmentioning
confidence: 86%
See 1 more Smart Citation
“…Table 3 shows the previous SCW flow around particle validation conclusions of our research group studies, 31,32 Wei et al, 22,38 and Zhang et al, 27,28 which shows the accuracy and reliability of the numerical model. Our group's previous studies 34,35,39 further showed more details for the multi-particle system. In summary, the accuracy of the calculation method adopted in this paper is verified, and it can be used in the subsequent numerical simulation calculation studies related to the particle layer.…”
Section: Numerical Model Validationmentioning
confidence: 86%
“…Our group had previously conducted studies on the drag force and heat transfer of single and two particles in SCW with different particle characteristics and considered the effect of Stefan flow, ,,, which does not address the issues of particles in a cluster situation. In this work, we adopt the multi-particle layer consisting of several individual particles with different particle layer solid holdups to simplify the multi-particle composition structure in the dense particle-laden flows, and the simulations resolve the flow field around each particle.…”
Section: Introductionmentioning
confidence: 99%